Psychometric Properties of the Chinese Version of the Functional Assessment of Self-Mutilation (FASM) in Chinese Clinical Adolescents - Qu, Diyang; Wang, Yanni; Zhang, Zhiguo; Meng, Linlin; Zhu, Feng; Zheng, Tiansheng; He, Kongliang; Zhou, Yue; Li, Chuanxiao; Bu, He; Zhou, Yongjie (Frontiers in Psychiatry, 2022)
Background: Functional Assessment of Self-Mutilation (FASM) is one of the most widely used tools assessing adolescent’s non-suicidal self-injury. However, the Chinese version of FASM is lacking. The present study aimed to adapt the FASM to the Chinese patients and examine its reliability and validity. Methods: The original English version of the FASM was translated into Chinese following Brislin's model of cross-culture translation, and then pilot study and cognitive interview were carried out with 15 adolescent patients to assess the acceptability and comprehensibility of all items. The items were subsequently tested in a sample of 621 Chinese adolescent patients recruited by 20 psychiatric or general hospitals in 9 provinces across China. We examined the distribution of responses for each item. Factor analysis, Cronbach's alpha and McDonald's omega, intraclass coefficient, and Spearman's rank correlations were deployed to assess the dimensional structure, internal consistency reliability, test-retest reliability and criterion validity. Results: The final adapted Chinese version of FASM (C-FASM) included a 10-item method checklist and a 15-item function checklist of NSSI, and other characteristics of NSSI. C-FASM exhibited acceptable internal consistency (Cronbach's α=0.81 and Ω=0.80 for method checklist; Cronbach's α=0.80 and Ω=0.76 for function checklist) and test-retest reliability (method checklist:0.79; function checklist:0.87). Factor analysis for NSSI functions yielded a three-factor model with a good model fit. In addition, the instrument showed an expected correlation with the instrument of the Deliberate Self-Harm Behavior Inventory (r = 0.84, p <0.001). Conclusions: The C-FASM has good content, structural validity and reliability. The instrument can be helpful to Chinese adolescents as a comprehensive measure of NSSI behaviors.